A brief comment on Maxwell(/Newton)[-Huygens] spacetime. (August 2018) - Weatherall, James Owen
Abstract: I provide an alternative characterization of a "standard of rotation" in the context of classical spacetime structure that does not refer to any covariant derivative operator. Highlights: I provide a novel characterization of a standard of rotation in classical spacetime. I establishing its relationship with the standard definition given by Earman. I develop an alternative way of treating spatial geometry in classical spacetimes.